Partial Regression of Congenital Brain Stem Glioma and Its Outcome - Kadam, Sandeep; Chavan, Rajendra; Kadam, Archana; Patole, Sanjay (Journal of Pediatric Neurology, 2021)
Congenital brain stem gliomas are rare in neonates and are difficult to diagnose given their subtle clinical presentation. They are usually associated with poor prognosis by their location and behavior. However, there are few reports of spontaneous regression of brain stem glioma with favorable long-term outcome. In this article, we reported a case of congenital brain stem glioma with a normal long-term outcome where a wait and watch approach allowed observation of spontaneous partial regression of the tumor with normal neurodevelopmental outcome at 40 months of age. The optimal approach to the management of children with brain stem glioma is difficult to define as, in general, the prognosis is considered poor. Selecting an “early intervention” or “wait and watch” approach depends on the nature, size, and progression of the lesion, and the risk versus benefits of early intervention. The clinical course of our case suggests that a conservative approach may be justified in selected cases as long as the parents have been counselled and regular frequent follow-up is assured.
Keywords: neonate; congenital; brain tumor; outcome